TRANSFORMASI KULTURAL DAN REKONSTRUKSI GENDER: ANALISIS TURNING POINT TOKOH IREWA DALAM NOVEL ISINGA KARYA DOROTHEA ROSA HERLIANY - Prih Nur Fia Istiqomah; Mohammad Kanzunnudin; Ahmad Hariyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the persistence of the patriarchal system that shapes gender inequality, particularly within the Papuan cultural context represented in the novel Isinga. The objective of this study is to analyze the process of gender reconstruction and the manifestation of cultural radical feminism in overcoming gender injustice through the character Irewa. The research method employed is qualitative descriptive with a feminist literary approach. Data were collected through documentation with interpretive reading and note-taking techniques, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The results show that gender reconstruction occurs through three systematic transformation stages: the construction stage (oppression), the transition stage (turning point involving the emergence of critical awareness in the character Irewa), and the realization stage (economic independence and courage in public speaking). Cultural radical feminism is manifested through reclaiming control over the body, rejecting violence, and transforming cultural narratives via the